Study in the Responses of-Some Soybean (Glycine max L.) Cultivars Under Water Stress Condition - EDI PURWANTO (Biodiversitas Journal of Biological Diversity, 2003)
These sets of experiments were conducted at Faculty of Agriculture Sebelas Maret University and the Central Experiment Station of Agricultural Faculty, Sebelas Maret University at Jumantono, Karanganyar, Central Java. The experiments were conducted under greenhouse, laboratory and field condition for each year, while the duration of this research was for two years. The specific objectives of the experiments were: (i) to determine the changes of some morpho-physiological characteristics of water stress soybean and those of unstressed plants at different growth stages; (ii) to evaluate relationship between morpho-physiological traits associated with water stress resistance and yield of soybean. In this study consists some experiments, there are: (i) about response of some soybean cultivars to water stress in screen house and field condition; (ii) about germination response of some soybean cultivars in different concentration 0f PEG; (iii) a bout recovery survival and recovery of soybean seedlings after heat treatment. The plants were well watered before thetreatment. Based on the result of the experiments, the following conclusion could be made: (i) water stress reduced growth, yield and yield components 0 f a II soybean c ultivars used; (li) PEG induced water stress resulted in lower germination, shorter root and shoot length, and increase root-shoot ratio; (iii) the ability of plants to recovery after heat stress have low correlation with drought resistance in this experiment; (iv) the determination of root-shoot ratio in the seedling stage was shown to be suitable screening techniques used to study water stress resistance.Â© 200'3Jurusan Biologi FMIPA UNS SurakartaKey words: soybean (Glycine max L.), cultivars, water stress.